Fallout. Season two [videorecording (DVD)] - Wagner, Graham; Robertson-Dworet, Geneva (Amazon MGM Studios, 2026)
Lucy and Maximus both had to face some difficult truths about what they were seeking, and putting those things behind them, begin to forge a new way forward. Lucy joins the Ghoul on his quest to find his family as Maximus returns to the Brotherhood with Cold Fusion, Thaddeus as a ghoul creates a lucrative outlet, and Norm finds his way into middle management and out of the vaults. Dogbreath lives.